2011
DOI: 10.3354/meps09178
|View full text |Cite
|
Sign up to set email alerts
|

Resolving natal tags using otolith geochemistry in an estuarine fish, rainbow smelt Osmerus mordax

Abstract: Sr) varied significantly among locations (n = 9) and provided 83% crossvalidated accuracy using a quadratic discriminant function analysis. Assignments based only on the 3 isotope variables resulted in the highest rates of correct assignment (87%), largely driven by a significant increase (~11%) in correct assignments at nearby locations (< 20 km distant). Five of the 7 elements examined were significantly correlated with each other, consistent with a common response to estuarine differences. We also observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…In conclusion, we have shown that significant differences in elemental signatures of mussel shells exist on 50 km scales throughout the Gulf of Maine, which should allow us to use elemental fingerprinting to identify natal origins and estimate patterns of blue mussel dispersal in the region. Although, to date, researchers are still in the process of confirming the viability of this “new wave” technique [50] of elemental fingerprinting (e.g., [26] , [27] , [35] , [36] , [51] ), it has the potential to permit testing of important questions in global change biology, including whether oceanographic processes will preclude or facilitate climate-induced shifts in distributions of marine species. Ideally, future use of elemental fingerprinting for characterizing mussel dispersal patterns would maximize study area, coverage of that area (i.e., number of collection sites), and sampling frequency while also integrating genetic and/or flow dynamic approaches to best shed light on the “black box” of larval connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we have shown that significant differences in elemental signatures of mussel shells exist on 50 km scales throughout the Gulf of Maine, which should allow us to use elemental fingerprinting to identify natal origins and estimate patterns of blue mussel dispersal in the region. Although, to date, researchers are still in the process of confirming the viability of this “new wave” technique [50] of elemental fingerprinting (e.g., [26] , [27] , [35] , [36] , [51] ), it has the potential to permit testing of important questions in global change biology, including whether oceanographic processes will preclude or facilitate climate-induced shifts in distributions of marine species. Ideally, future use of elemental fingerprinting for characterizing mussel dispersal patterns would maximize study area, coverage of that area (i.e., number of collection sites), and sampling frequency while also integrating genetic and/or flow dynamic approaches to best shed light on the “black box” of larval connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Similar profiles within individuals of one haul but different from another haul can be expected if fish stay together in one school for most of their life and encounter similar circumstances as they move around. Alternatively the similar patterns are caused by the 88 Sr signature of the specific region, which would indicate that smelt do not move around a lot, a finding which shows agreement with a closely related species the rainbow smelt Osmerus mordax [25], [26], [27] …”
Section: Discussionmentioning
confidence: 89%
“…Certaines ont tenté plus particulièrement de mettre en relation la composition élémentaire des otolithes avec celle de l'eau (Bath et al, 2000;Elsdon et Gillanders, 2003;Milton et Chenery, 2001 (Brazner et al, 2004b). Jusqu'à présent, l'empreinte élémentaire a surtout été utilisée en milieux marins (Brown, 2006;Campana et al, 2007;Clarke et al, 2009;Cook, 2011;Edmonds et al, 1991;Fodrie et Herzka, 2008;Gillanders et Kingsford, 1996;Humphreys Jr et al, 2005;Lawton et al, 2010;Rooker et al, 2002;Thorrold et al, 2007), dans certains estuaires (Bradbury et al, 2011;Brown, 2006;Gillanders et Kingsford, 1996;Hobbs et al, 2007;Swearer et al, 2003) et seulement quelques recherches comparables ont été menées en eaux douces avec succès (Brazner et al, 2004a;Brazner et al, 2004b;Fisher et al, 1999;Whitledge, 2009;Zeigler et Whitledge, 2010;Zeigler et Whitledge, 2011;Zitek et al, 2010). heures pour un séchage complet, puis rangées dans une boîte en vue de procéder aux analyses à l'aide d'un spectromètre de masse couplé à un plasma inductif (Tableau 2).…”
Section: Remerciementsunclassified